Food allergies around the world - Wong, Gary Wing-Kin (Frontiers in Nutrition, 2024)
The increase in the prevalence of food allergy has been considered as the second wave in the allergy epidemic following the first wave of increase in asthma and allergic rhinitis. It is well known that the prevalence of allergic conditions would follow economic development and urbanization in many countries or regions. In developed countries, one in three children suffered from at least one allergic disorder and these conditions include food allergy, eczema, allergic rhinitis and asthma. Food allergy is very often the first allergic manifestation affecting infants and young children. The exact etiologies are not known. The clinical manifestations ranged from a simple rash or an itch around the mouth, to the more severe manifestations of angioedema and potentially fatal anaphylaxis. Among all cases of childhood anaphylaxis, food is the most common cause. The common allergens resulting in food allergies in developed countries include egg, milk, fish, wheat, peanuts and tree nuts. However, there are marked variations in the patterns of food allergens in developing countries. In line with the epidemiology of asthma, food allergy is also much less common in rural areas. Clear understanding of reasons explaining the disparity of food allergies between urban and rural population would pave the way to the development of effective primary prevention for food allergy.